Role of Canva in Improving Arabic Speaking Skills: A Literature Review - Al Muhibbin, Fateh; Koderi, Koderi; Kesuma, Guntur Cahaya; Gahazi, Fachrul; Zikrillah, Zikrillah (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2025)
This study is motivated by challenges in learning Arabic speaking skills (Maharah al-Kalam), such as less interactive teaching methods, limited learning media, and low student motivation. Along with the development of technology, the utilization of digital platforms such as Canva is considered an innovative solution to improve speaking skills in Arabic. This study aims to analyze the role of Canva in the development of Maharah al-Kalam through a literature review of various previous studies. The method used is a literature review by examining various studies that discuss the effectiveness of Canva in Arabic language learning. The results showed that Canva can be an interesting and interactive learning media, helping students to enrich their vocabulary, increase their confidence, and improve their pronunciation in speaking Arabic. In addition, Canva can be applied in flipped classroom-based learning models and other technology-based approaches to strengthen students' learning experience. The contribution of this study is to provide insights into effective strategies in utilizing Canva to improve Arabic speaking skills as well as highlighting the challenges in its implementation. The implication of this study shows that the integration of Canva in Arabic language learning can be a strategic step for educators in developing technology-based learning methods that are more interactive and communicative.